Longitudinal molecular analysis of clinical and fecal Escherichia coli isolates at a Veterans Affairs Medical Center in Minnesota, USA, 2012–2019 - Clabots, Connie; Thuras, Paul; Johnson, James R. (Frontiers in Microbiology, 2024)
Extraintestinal Escherichia coli infections -an ever-growing public health threat -are commonly studied without regard for temporal patterns of infection, phylogenetic and clonal background, or the host gut E. coli population, despite these factors' likely importance. Here, we analyzed > 7000 clinical E. coli isolates from patients at the Minneapolis Veterans Affairs Health Care System (2012-2019), and concurrent fecal E. coli from uninfected veterans. We assessed phylogenetic group distribution, membership in selected sequence types (STs) and subsets thereof -including the pandemic, resistance-associated ST131-H30R and ST1193 lineages -and strain type, as defined by pulsed-field gel electrophoresis. We then compared these features with temporal patterns of infection in individual hosts. H30R was the leading lineage, both overall and among fluoroquinolone-resistant isolates; ST1193 followed, among fluoroquinolone-resistant isolates. Recurrences were common (31% of subjects, 41% of episodes) and repeated (up to 23 episodes per subject; up to 2655d post-index), and usually involved the subject's index strain (63% of recurrences), even at extra-urinary sites. ST131, H30R, ST1193, and fluoroquinolone-resistant strains generally caused significantly more recurrences than did other strains, despite similar recurrence intervals. ST131 strain types shifted significantly over the study period. Infection-causing strains were commonly detectable in host feces at times other than during an infection episode; the likelihood of detection varied with surveillance intensity and proximity to the infection. H30R and ST1193 were prominent causes of fecal-clinical clonal overlap. These findings provide novel insights into the temporal and clonal characteristics of E. coli infections in veterans and support efforts to develop anticolonization interventions.